(untitled) (Quinto Sol, 2016)
In this article the main findings of the first investigation about the group Command of Organization of the Peronist Youth are presented. It begins by rebuilding the militant networks out of which emerged activists, led by Peronist leader Alberto Brito Lima, that founded the group. A description and analysis is made concerning those political, ideological, sociological and cultural characteristics that are identified as the most relevant ones for the purposes of making a characterization of the Command of Organization. It is shown how the death of several of its members in politically violent episodes, gave place to the construction of a martyrdom that was functional to the recreation of a heroic mystique that fueled a combative militancy ideologically associated to a nationalist imaginary.The reconstruction of the history of this group, born in the early sixties, gives us information that we consider significant to interpret the belligerent internal differences within Peronism occurred in the first half of the seventies. Since these Peronist activists played a protagonic role in these events, their analysis provides us with elements to make intelligible the dynamics of the controversial historical period marked by the phenomenon of political violence.